Insight into the thermal transport by considering the modified Buongiorno model during the silicon oil-based hybrid nanofluid flow: probed by artificial intelligence - Ullah, Asad; Yao, Hongxing; Ullah, Farid; Alqahtani, Haifa; Ismail, Emad A. A.; Awwad, Fuad A.; Shaaban, Abeer A. (Frontiers in Physics, 2024)
This work aims to analyze the impacts of the magnetic field, activation of energy, thermal radiation, thermophoresis, and Brownian effects on the hybrid nanofluid (Ag+TiO_2+Silicon oil) flow past a porous spinning disk. The pressure loss due to porosity is constituted by the Darcy-Forchheimer relation. The modified Buongiorno model is considered for simulating the flow field into a mathematical form.